Command at sea : naval command and control since the sixteenth century - Palmer, Michael A. (Harvard University Press, 2005)
In this grand history of naval warfare, Palmer observes five centuries of dramatic encounters under sail and steam. From reliance on signal flags in the seventeenth century to satellite communications in the twenty-first, admirals looked to the next advance in technology as the one that would allow them to control their forces. But while abilities to communicate improved, Palmer shows how other technologies simultaneously shrank admirals' windows of decision. The result was simple, if not obvious: naval commanders have never had sufficient means or time to direct subordinates in battle.